PENGARUH PENERAPAN MODEL KOOPERATIF TIPE THINK PAIR SQUARE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Putri, Zakia Rahima (Departemen Matematika, 2023)
Concept understanding is a very important ability in the mathematics learning process that is expected to be mastered well by learners. The real life in the field found that the understanding of the concept of mathematics among the class VIII students of SMP Negeri 5 Mandau for the 2022–2023 academic year was still low. One effort that can be made to improve students' concepts understanding of mathematical is to apply models such as Think-Pair-Square learning. The purpose of this research is to describe whether the understanding of the mathematical concepts of students who learn using the Think Pair Square learning model is better than the understanding of the mathematical concepts of students who learn by using the direct learning model in class VIII SMP Negeri 5 Mandau. This research type is quasi-experimental with a randomized, control-group-only design. This study's population consisted of students in class VIII at SMP Negeri 5 Mandau. Class VIII.4 was selected as the class for experimental and class VIII.2 as the class for control. The instrument used is an understanding test of mathematical concepts in consist of description questions. Keywords —Cooperative Learning, Mathematical Concept Comprehension, Think Pair Square, Direct Learning.